Aportes conceituais sobre a dialética inclusão/exclusão: possibilidades de convivência com a diversidade no espaço escolar - Ribeiro, Vagno Batista (2013)
Inclusive Education in contemporaneity expresses one of the desires of a society which still stigmatizes and discriminates against people with special educational needs. Greater dignity, respect and integration are what the Brazilian inclusive education policies seek to propitiate for its society. Their greatest challenge is to transform the installed prejudiced mentality through actions of education professionals to change this situation. Faced with this challenge of schools being structured to work with homogeneity and never with diversity the goal of this paper is to defend the perspective of inclusive education aiming at the construction of a school for all, focusing on the dialectic of inclusion/exclusion. That is why its origins, its levels, its consequences as well as its incoherencies will be thematicized through descriptive, theoretical research which characterizes the danger of an inclusion which does not take into account the differences of the daily situations of the education professionals. Taking into account the conceptual paradigms and principles which are increasingly being defended in national and international documents, inclusion is a movement of global scope which gathers together people struggling for the people with special educational needs (PNEES) and their families in their quest for their rights and a place in society. However, what can actually be considered inclusion? What makes education professionals have such different comprehensions and meanings of this issue? And what are the main difficulties encountered from a conceptual point of view?